Impedance spectroscopy analysis of TiO2 thin film gas sensors obtained from water-based anatase colloids - Ponce, Miguel Adolfo (2009)
In this work impedance spectroscopy technique was employed in order to characterize the gas-sensing behavior of undoped titanium dioxide (TiO2) polycrystalline thin films. The electrical measurements were performed in a sensor-testing chamber that allows independent control of temperature, pressure, gas composition and flow rate. Frequency measurements, in the range from 40 Hz to 110 MHz, were performed in order to evaluate the gas sensor response of the samples as a function of temperature (50–350 °C) and surrounding atmosphere (vacuum or air at atmospheric pressure). Impedance spectroscopy is a very useful and important technique due to the possibility of using this method for discriminating between grain boundary capacitance (Cgb) and grain boundary resistance (Rgb) contributions. Therefore, a simple model taking into account variations in the intergranular potential barriers is proposed in this work.